2016
DOI: 10.1128/jcm.02113-15
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Anti-Elicitin Antibody-Based Immunohistochemical Assay for Diagnosis of Pythiosis

Abstract: Pythiosis is an emerging and life-threatening infectious disease of humans and animals living in tropical and subtropical countries and is caused by the fungus-like organism Pythium insidiosum. Antifungals are ineffective against this pathogen. Most patients undergo surgical removal of the infected organ, and many die from advanced infections. Early and accurate diagnosis leads to prompt management and promotes better prognosis for affected patients. Immunohistochemical assays (IHCs) have been developed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
(45 reference statements)
1
18
0
Order By: Relevance
“…As opposed to the standard stains (i.e., GMS, PAS and H&E), several immunohistological staining assays have been developed to facilitate microscopic detection of P. insidiosum (Inkomlue et al, 2016;Keeratijarut et al, 2009;Triscott, Weedon & Cabana, 1993;Mendoza, Ajello & McGinnis, 1996;Mendoza, Kaufman & Standard, 1987;Brown et al, 1988). These assays rely on the use of rabbit antiserum generated against crude protein extract of P. insidiosum.…”
Section: Histological Examinationmentioning
confidence: 99%
See 2 more Smart Citations
“…As opposed to the standard stains (i.e., GMS, PAS and H&E), several immunohistological staining assays have been developed to facilitate microscopic detection of P. insidiosum (Inkomlue et al, 2016;Keeratijarut et al, 2009;Triscott, Weedon & Cabana, 1993;Mendoza, Ajello & McGinnis, 1996;Mendoza, Kaufman & Standard, 1987;Brown et al, 1988). These assays rely on the use of rabbit antiserum generated against crude protein extract of P. insidiosum.…”
Section: Histological Examinationmentioning
confidence: 99%
“…A novel immunohistological method targeting elicitins that are only present in oomycetes, including P. insidiosum (Jiang et al, 2006;Lerksuthirat et al, 2015), has been reported to be highly specific. Recently, Inkomlue et al used a rabbit antiserum against recombinant elicitin (ELI025) of P. insidiosum for the development of an immunohistochemical assay (Inkomlue et al, 2016), and found that all 38 P. insidiosum samples were detected, but not 49 control samples of various fungi, including Fusarium species and Mucorales.…”
Section: Histological Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of P. insidiosum cannot rely solely on microscopic characteristics because this organism shares filamentous morphologies with true fungi (i.e., Aspergillus species, Fusarium species, and fungal species of the class Zygomycetes). Several immunodiagnostic tests (i.e., immunodiffusion, Western blot, hemagglutination, enzyme-linked immunosorbent assay, immunochromatography, and immunohistostaining assay) have been developed for direct detection of the anti-P. insidiosum antibodies in serum samples or the P. insidiosum hyphae in an infected tissue (Pracharktam et al, 1991;Mendoza et al, 1997;Krajaejun et al, 2002Krajaejun et al, , 2006aKrajaejun et al, , 2009Jindayok et al, 2009;Keeratijarut et al, 2009Keeratijarut et al, , 2013Supabandhu et al, 2009;Chareonsirisuthigul et al, 2013;Inkomlue et al, 2016;Intaramat et al, 2016;Lohnoo et al, 2018). In addition, a number of molecular-based assays (i.e., polymerase chain reaction and sequence homology analysis) can be used to detect the specific DNA sequence of P. insidiosum in clinical samples (Badenoch et al, 2001;Znajda et al, 2002;Vanittanakom et al, 2004;Krajaejun et al, 2011;Keeratijarut et al, 2014Keeratijarut et al, , 2015Rujirawat et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Isolation of the pathogen from infected tissues by the standard microbiological procedure is time-consuming and requires experience ( Chaiprasert et al, 1990 ). A number of detection tools such as serological tests ( Pracharktam et al, 1991 ; Krajaejun et al, 2002 , 2006a , 2009 ; Grooters et al, 2002 ; Jindayok et al, 2009 ; Supabandhu et al, 2009 ; Chareonsirisuthigul et al, 2013 ; Keeratijarut et al, 2013 ; Intaramat et al, 2016 ), immunostaining assays ( Keeratijarut et al, 2009 ; Inkomlue et al, 2016 ), and molecular biology methods ( Grooters & Gee, 2002 ; Botton et al, 2011 ; Keeratijarut et al, 2014 , 2015 ; Rujirawat et al, 2017 ), have been successfully developed for P. insidiosum infection. However, such tools are not generally available in non-reference clinical laboratories, resulting in missed or delayed diagnosis of pythiosis.…”
Section: Introductionmentioning
confidence: 99%